The Suppressive Effect of the Motor System on the Sensory System in Patients With Tourette Syndrome - Sun, Ying; Wei, Hua; Lin, Yicong; Wang, Yuping (Frontiers in Neurology, 2020)
Objective: Tourette syndrome (TS) is a complicated sensorimotor disorder. Some patients with TS relieve their involuntary premonitory urges via tics. However, the effect of the motor system on the sensory system has not yet been elucidated. The purpose of the present study was to investigate changes in the excitability of the sensory cortex following repetitive transcranial magnetic stimulation (rTMS) of the motor cortex in patients with TS. Methods: Twenty-nine patients with TS and twenty healthy, age-matched controls were enrolled in this study. All subjects were divided into four groups: patients with rTMS, patients with sham-rTMS, controls with rTMS and controls with sham-rTMS. The clinical severity of tics was evaluated using the Yale Global Tic Severity Scale. Single somatosensory evoked potentials (SEPs) and paired SEPs were recorded by stimulating the median nerve at the wrist of all subjects. The resting motor threshold (RMT) was tested in each subject in the rTMS group. Afterwards, all four groups were administered rTMS (1-Hz, 90% RMT) or sham-rTMS for 200 seconds, followed by a 15-minute rest. Finally, single SEPs and paired SEPs were repeated for each subject. Results: No significant differences in RMT, the amplitudes of single SEPs or the suppression of paired SEPs were observed between patients with TS and controls at baseline. After rTMS, a significant suppression of the peak-to-peak amplitude of the N20-P25 responses of single SEPs was observed in both controls (p=0.049) and patients (p<0.0001). The suppression of the N20-P25 peak-to-peak amplitude was more significant in patients than in controls (p=0.039). A significant difference in the suppression of paired SEPs after rTMS was not observed between groups. Conclusions: The more significant suppression of N20-P25 components of single SEPs with normal suppressed paired SEPs in patients with TS after 1-Hz rTMS of the motor cortex suggests that the suppressive effect of the motor system on the sensory system might originate from the motor-sensory cortical circuits rather than the sensory system itself.